Structural and Biochemical Responses of the Seagrass Halodule uninervis to Changes in Salinity in Kuwait bay, Doha Area - Al-Arbash, Alaa; Al-Bader, Dhia A; Suleman, Patrice (Kuwait Journal of Science, 2016)
The effect of salinity in Doha